From back streets to Olympic stage: The development of breaking and skateboarding in South Korea - Lee, E.; Tak, M. (The International Journal of the History of Sport, 2026)
Unlike traditional sports with well-documented origins and developmental paths, action sports have histories that are more undefined and fragmented. This article explores the development of breaking and skateboarding in South Korea, from street activities to Olympic disciplines. Analysing data from documents and semi-structured interviews with 15 individuals in the Korean action sports scene, this article presents three key findings. First, the growth of breaking was significantly influenced by a comic book Hip-Hop while the initiation of skateboarding owes much to foreigners visiting Korea, and international cinematic influences. Second, pioneers of these sports contended with several challenges, such as insufficient practicing places, informal training methods, and clannish subcultures, alongside a lack of recognition and career pathways. Third, despite these new sports` low status, their Olympic addition has undeniably increased recognition and popularity of these sports. From the results, this article argues that the development of breaking and skateboarding in South Korea was shaped by a confluence of cultural, social, and media influences, while their Olympic inclusion transformed them from niche activities into recognized sports. Without the Olympics` validation, these activities would likely have remained on the fringes of mainstream sports in South Korea.